2012
DOI: 10.3329/jhpn.v30i1.11270
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antimicrobial Resistance of Vibrio cholerae O1 Biotype El Tor Strains Isolated in a Tertiary-care Centre in India

Abstract: The antimicrobial susceptibility patterns are on constant change with the recent emergence of multidrug-resistant strains of most bacteria. Results of recent studies in India showed that most isolates of Vibrio cholerae O1 were resistant to the commonly-used antibiotics. The study was conducted to determine the antibiotic susceptibility patterns of V. cholerae O1 isolated during 2008-2010 at the hospital of the Jawaharlal Nehru Institute of Post Graduate Medical Education and Research, Puducherry, India. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
2
31
1
Order By: Relevance
“…As chloramphenicol is not being used commonly in routine since a long time, selection pressure is decreasing and increased susceptibility is recorded by isolates. Ciprofl oxacin susceptibility (100%) seen in the present study was similar to other studies by Mandal et al [10] (97%) and Shrestha et al [11] (100%) carried out in Puducherry and Nepal respectively. An antibiotic susceptibility result reported by Chander et al [12] was quite similar to the present study.…”
Section: Discussionsupporting
confidence: 82%
“…As chloramphenicol is not being used commonly in routine since a long time, selection pressure is decreasing and increased susceptibility is recorded by isolates. Ciprofl oxacin susceptibility (100%) seen in the present study was similar to other studies by Mandal et al [10] (97%) and Shrestha et al [11] (100%) carried out in Puducherry and Nepal respectively. An antibiotic susceptibility result reported by Chander et al [12] was quite similar to the present study.…”
Section: Discussionsupporting
confidence: 82%
“…There has been an increase in the incidence of antibiotic resistance in O1, O139 and non-O1 V. cholerae serogroups in both clinical and environmental isolates (Deashinta et al, 2007;Mandal et al, 2012;Rahmani et al, 2012;Panda et al, 2012). V. cholerae O1 strains that are resistant to cefotaxime, nalidixic acid, streptomycin, tetracycline and trimethoprim have been isolated from south India (Jagadeeshan et al Cholera has been categorized as one of the emerging and reemerging diseases that cause severe diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio strains having resistance against cephalosporins have been reported scarcely [15], while the current study elicited alarming resistance rates against cephalosporin class in the region. The previous studies reported very higher levels of resistance against nalidixic acid, streptomycin, and ciprofloxacin antibiotics [31,32,43,44]; however, our study implicated relatively low levels of resistance against these antibiotics.…”
Section: Discussionmentioning
confidence: 87%
“…Isolation of multidrug resistant Vibrio species from clinical sources is a major concern. Recent studies have reported a rise in antimicrobial resistance in Vibrio species against major classes of antibiotics (aminoglycosides, tetracyclines, and b-lactams) [14,15].…”
Section: Introductionmentioning
confidence: 99%